The ribosomal repeat of Aspergillus niger and its effects on transformation frequency - M. J. O'CONNELL; C. E. A. DOWZER; J. M. KELLY (Fungal Genetics Reports, 1990)
The ribosomal RNA genes have been used in studies of a variety of phenomena. These include studies of molecular phylogeny, transcription, recombination and transformation. In Saccharomyces cerevisiae, where integrative transformation is achieved by homologous recombination, the presence of the ribosomal repeat unit in the transformation vector greatly increases the frequency of transformation (Szostak and Wu 1979. Plasmid 2:536- 554; Smolik-Utlaut and Petes 1983. Mol. Cell. Biol. 3:1204-1211). In the filamentous fungus Aspergillus nidulans, where integrative transformation can be achieved either via homologous or heterologous recombination, the presence of ribosomal repeat sequences in the transformation vector has no effect on the frequency of transformation (Tilburn et al. 1983. Gene 26:205-221). [Ed.: This is also the case in Neurospora crassa: Russell et al. 1989. BBA 1008:243-246]. Here we report the molecular cloning of the ribosomal repeat unit from Aspergillus niger. We have found that the presence of cloned ribosomal DNA sequences from A. niger increases the frequency of transformation in A. niger.